Rust programming master class from beginner to expert. (Packt Publishing, 2022)
Develop beginner to advanced level skills in Rust programming About This Video Learn the basic syntax of Rust and its feature of memory safety Develop an understanding of advanced level concepts such as generics, traits, lifetimes, and closures Gain hands-on experience in solving some intermediate to advanced level problems using Rust In Detail Most programming languages involve trade-offs. Low-level languages such as C and C++ typically sacrifice memory safety for speed and control. High-level languages, however, such as Python or JavaScript, are safer but less effective from a power and speed standpoint. We get the best of both worlds with Rust. More specifically, it is a system programming language, which implies that while it has speed and control, it also has safety features, making it far better than high-level languages in this regard. Rust stands out from all other programming languages because of this. You will progress through this course from basic to expert level. This course is created from the viewpoint of a student who is new to Rust and does not have any prior understanding of it. We cover a wide range of knowledge and skills in this extensive course, including the fundamentals of Rust programming syntax; primitive and non-primitive types; common Rust collectors; Enums; traits and structures; generics, lifetimes, and closures; the Rust module system; learning how to use external crates; and publishing crates. By the end of this course, you will have mastered Rust programming to the point where you can code with confidence and professionalism. Audience Anyone wishing to achieve a solid programming profession with strong Rust coding skills should take this course. As this is beginner-level training, we start from the beginning and do not require any prior Rust experience.